STUDIES ON THE APPLICATION OF DYAR’S AND PRZIBRAM’S RULE TO THE DEVELOPMENT OF MULBERRY SILKWORM RACE NISTARI BOMBYX MORI LINN. - SINGH, T.; DAS, S. K.; RAO, G. SUBBA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1989)
The present investigation was undertaken to study the application of Dyar's and Przibram's rule in the light of development of different larval instars of an indigenous mulberry silkworm race, Nistari B. mori L. Growth trend in the body length and head width indicated a linear progression after Dyar's. The growth ratio for body weight at each successive instar exceed the value required under Przibram's theory. The body length, head width and body weight increases 18461, 12.309 and 10165 folds respectively from hatching to matured larvae.